Asal Usul Bahasa Dan Perkembangannya Dalam Komunikasi Manusia: Asal Usul Bahasa Dan Perkembangannya Dalam Komunikasi Manusia - Airin, Suci Pratiwi; Dina warohmah; Silvina Noviyanti; Naswa Nabila Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT The origin and development of language in human communication is a fascinating and complex topic. This study aims to examine various theories regarding the origin of language, from imitation of natural sounds and animal calls, social convention theories, to theological perspectives. The method used is a literature review, analyzing credible written sources such as books, journals, and scientific articles. The findings indicate that language evolved from primitive nonverbal communication into a complex symbolic system, influenced by biological, social, and cultural factors. Language is not only a communication tool but also a reflection of cultural identity and historical legacy. This research provides insights into the social, cultural, and technological dynamics that drive language development in human interaction.